1, 10‐Phenanthroline Ruthenium(II) Complexes as Model Systems in the Search for High‐Performing Triplet Photosensitisers: Addressing Ligand versus Metal Effects. Issue 12 (13th December 2017) - Lu, Yue; Conway‐Kenny, Robert; Twamley, Brendan; McGoldrick, Niamh; Zhao, Jianzhang; Draper, Sylvia M.
Abstract: The front cover artwork is provided by R. Conway‐Kenny of the Draper Synthetic Materials Group in Trinity College Dublin (Ireland). The image concept is based on "chemically shopping for the right accessory". For coordination chemists the metal complex is the model and s/he needs to be dressed appropriately depending on the occasion. Read the full text of the Article at10.1002/cptc.201700158 . Abstract : "A series of Ru II complexes with 1, 10‐phenanthroline ligands bearing triphenylamine and/or pyrene chromophores were investigated in triplet photosensitising applications …" This and more about the story behind the front cover can be found in the Article at10.1002/cptc.201700158 .